2019
DOI: 10.1021/acs.jpclett.9b00595
|View full text |Cite
|
Sign up to set email alerts
|

Tuning Optical and Electronic Properties in Low-Toxicity Organic–Inorganic Hybrid (CH3NH3)3Bi2I9 under High Pressure

Abstract: Low-toxicity, air-stable methylammonium bismuth iodide (CH3NH3)3Bi2I9 has been proposed as a candidate to replace lead-based perovskites as highly efficient light absorbers for photovoltaic devices. Here, we investigated the effect of pressure on the optoelectronic properties and crystal structure of (CH3NH3)3Bi2I9 up to 65 GPa at room temperature. We achieved impressive photoluminescence enhancement and band gap narrowing over a moderate pressure range. Dramatic piezochromism from transparent red to opaque bl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
45
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 39 publications
(46 citation statements)
references
References 55 publications
(78 reference statements)
1
45
0
Order By: Relevance
“…[99] By introducing MAI as vapor instead of as solution, the PL quantum yield (PLQY) was measured up to 0.4%, and its PL lifetime increased to 760 ps (Figure 4d). [89] In addition, Zou et al [100] found that the bandgap of MA 3 Bi 2 I 9 could be reduced under high pressure, and a phase transition from hexagonal P6 3 /mmc to monoclinic P2 1 occurred at 5.0 GPa. MAI reacting with BiI 3 at a stoichiometric ratio of 1:3 could generate an MABi 3 I 10 compound.…”
Section: Crystal Structure and Optoelectronic Propertiesmentioning
confidence: 99%
“…[99] By introducing MAI as vapor instead of as solution, the PL quantum yield (PLQY) was measured up to 0.4%, and its PL lifetime increased to 760 ps (Figure 4d). [89] In addition, Zou et al [100] found that the bandgap of MA 3 Bi 2 I 9 could be reduced under high pressure, and a phase transition from hexagonal P6 3 /mmc to monoclinic P2 1 occurred at 5.0 GPa. MAI reacting with BiI 3 at a stoichiometric ratio of 1:3 could generate an MABi 3 I 10 compound.…”
Section: Crystal Structure and Optoelectronic Propertiesmentioning
confidence: 99%
“…Pressure is a powerful and convenient strategy to alter the crystalline structure and electronic properties of 2D perovskite materials that are sometimes inaccessible by chemical tuning. [15][16][17][18][19][20][21] Depending on the applied pressure, the (BA) 2 (MA) n− 1 Pb n I 3n + 1 homologous series shows typical structural transition, which is accompanied by noticeable transformation in the optical properties of these materials. 22,23 The model (EDBE)CuCl 4 undergoes an αto-β phase transition, triggering a color change from yellow to orange when pressure increases from 0.3 to 4.9 GPa.…”
Section: Introductionmentioning
confidence: 99%
“…[112] The bandgap varies from 2.09 eV at ambient pressure and narrows at rate of 23.5 meV GPa À1 below 5 GPa and of 76.3 meV GPa À1 at higher pressure indicating a possible change in the electronic structure. [112] At 13.2 GPa the bandgap reaches a value of 1.35 eV. The variation in the bandgap can be related with piezochromism with the sample changing color from transparent red at ambient pressure to opaque black at 11 GPa.…”
Section: Other Structuresmentioning
confidence: 97%
“…The variation in the bandgap can be related with piezochromism with the sample changing color from transparent red at ambient pressure to opaque black at 11 GPa. [112] At ambient conditions, MA 3 Bi 2 I 9 crystallizes in a P6 3 =mmc phase, characterized by face-sharing Bi 2 I 9 clusters separated by MA cations, thus assuming a structure clearly different from the 3D perovskite structure, with slightly distorted BiI 6 octahedra with three longer equivalent bridging Bi-I bonds and three shorter equivalent terminal Bi-I bonds along the c direction. [112] At 5 GPa MA 3 Bi 2 I 9 transforms into the P2 1 phase, and the BiI 6 octahedron becomes more distorted because the organic cations are ordered and gain a preferential orientation along the b axis.…”
Section: Other Structuresmentioning
confidence: 99%